1983
DOI: 10.1111/j.1432-1033.1983.tb07518.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Proteolipids

Abstract: Proteolipid apoproteins have been isolated from a whole bovine brain homogenate by chloroform/methanol extraction, and fractionated by chromatography on modified (lipophilic) Sephadex, followed by ion-exchange chromatography on CM-Trisacryl. The various final, highly hydrophobic, fractions are homogeneous (sodium dodecyl sulfate/polyacrylamide gel electrophoresis). Transmembrane ion transfers were studied by 22Nat flux and electrical conductance measurements. Single channel events were observed at low protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Total bovine brain proteolipids and pure bovine MMPL were obtained as described in [12]. Pure bovine DM-20 was purified as described in [12] or 1131.…”
Section: Imm~~izat~onmentioning
confidence: 99%
See 1 more Smart Citation
“…Total bovine brain proteolipids and pure bovine MMPL were obtained as described in [12]. Pure bovine DM-20 was purified as described in [12] or 1131.…”
Section: Imm~~izat~onmentioning
confidence: 99%
“…Pure bovine DM-20 was purified as described in [12] or 1131. Myelin and total rat brain proteolipids were obtained from adult Wistar rats as reported [14, 151. Two rabbits were injected subcutaneously on days 0,20 and 48 with 300 ~1 of a solution containing 1 mg of synthetic peptide 117-129 coupled to KLH and 300 @I of either Freund's complete adjuvant (day 0) or incomplete adjuvant (days 20 and 48).…”
Section: Imm~~izat~onmentioning
confidence: 99%
“…After lipid removal and ether precipitation, mediatophore lost its activity but became water soluble as has been found to be the case for proteolipids (31)(32)(33)(34); this permitted us to determine the Stokes radius, the sedimentation coefficient, and to calculate a molecular mass of 210 ± 16 kDa. The method introduces large possible errors, because a difference of 0.75 S for sedimentation coefficient gives a difference of =20 kDa for molecular mass.…”
mentioning
confidence: 92%
“…In one study, the conductance across an artifi cial lipid bilayer measured by transmembrane " Na* flux was increased by incorporation of a proteolipid purified from whole brain homogenate [117], Although this PLP was not positively identified, it had a molecular mass of 24 kD, an N-terminal glycine and a C-tenninal phenyl alanine, characteristics of myelin PLP. In other studies, dicyclohexylcarbodiimide, an inhibitor of proton translo cation, was shown to preferentially bind the myelin PLP and to inhibit proton translocation in liposomes contain ing myelin PLP [122,123], This finding was later con firmed and shown not to be due to contamination with the PLP subunit of the mitochondrial Fo-ATPase which has similar binding properties [89].…”
Section: Other Roles For Plpmentioning
confidence: 99%
“…Among the most likely possibilities, and one for which some experimental evidence exists, is that myelin Dev Ncurosci 1996;18:297-308PLP may form part of an ion channel or pore complex within cell membranes and myelin. Other PLPs seem to be involved in channel formation in the sarcoplasmic reticulum Ca3'-ATPase, yeast membrane H*-ATPase, kidney Na'-KZ-ATPase and mitochondrial Fo-ATPase [41,117,118]. Additionally, the reputed structure of myelin PLP/DM-20 is homologous with a large group of proteins which also contain 4 membrane-spanning regions and which function as ion channels.…”
Section: Other Roles For Plpmentioning
confidence: 99%